How altruistic is indirect reciprocity? - Evidence from gift-exchange games in the lab - Johannes Becker; Daniel Hopp; Karolin Süß (ZBW - Leibniz Information Centre for Economics, 2020)
Indirect reciprocity is defined as a specific kind of behavior: An agent rewards or penalizes another agent for having behaved kindly or unkindly toward a third party. This paper analyzes the question of what drives indirect reciprocity: Does the agent reward or penalize because she (altruistically) cares for the third party? Or does she take the other agent's behavior as a signal of how the latter would treat her if they met? In order to measure the relative importance of the altruism motive versus the signaling motive, we consider a gift-exchange game with three players: an employer pays wages to a worker and a coworker, before the worker (but not the coworker) may reciprocate by exerting effort. We offer a theoretical framework to analyze both motives for indirect reciprocity and run a series of lab experiments. The treatments manipulate the worker's information on wages. We find that, if only the coworker's wage is observable, the worker's effort increases in the coworker's wage. In contrast, if the worker can observe her own wage, the coworker's wage does not affect worker effort at all. We interpret this as support for the signaling motive: Indirect reciprocity is rather a byproduct of direct reciprocity than an act of altruism.
Keywords: A13; C92; D91; J31; 330; gift-exchange; indirect reciprocity; signaling